Cisplatin Primary Complex with l‐Histidine Target Revealed by IR Multiple Photon Dissociation (IRMPD) Spectroscopy. Issue 3 (30th December 2016) - Corinti, Davide; De Petris, Alberto; Coletti, Cecilia; Re, Nazzareno; Chiavarino, Barbara; Crestoni, Maria E.; Fornarini, Simonetta
Abstract: The primary complex obtained from cisplatin andl ‐histidine in water has been detected and isolated by electrospray ionization. The so‐obtained cis ‐[PtCl(NH3 )2 (histidine)] + complex has been characterized in detail by high‐resolution mass spectrometry (MS), tandem MS, IR multiple photon dissociation (IRMPD) spectroscopy, and by quantum chemical calculations. The structural features revealed by IRMPD spectroscopy indicate that platinum binds to the imidazole group, which presents tautomeric forms. Thus, depending on the position of the amino acid pendant on the imidazole ring, isomeric complexes are formed that are remarkably different with respect to the ease with which they undergo fragmentation when activated either by energetic collisions or by multiple IR photon absorption. It is shown here how IRMPD kinetics can allow their relative proportions to be estimated. Abstract : Targeted attack : Cisplatin attack onl ‐histidine, a prime biological target, is directed to Nπ and Nτ atoms of the imidazole group in a ratio that is revealed by IRMPD kinetics.